2018
DOI: 10.1165/rcmb.2017-0008oc
|View full text |Cite
|
Sign up to set email alerts
|

CD34 Differentially Regulates Contractile and Noncontractile Elements of Airway Reactivity

Abstract: Airway hyperresponsiveness (AHR), a major hallmark of asthma, results from alterations of contractile and noncontractile elements of airway reactivity. CD34 is a sialomucin that is expressed on various cells involved in asthma, such as eosinophils and airway smooth muscle precursors, highlighting its potential influence in AHR. To study the role of CD34 in regulating the contractile and noncontractile elements of AHR, AHR was induced by chronic exposure to house dust mite (HDM) antigen. To assess the role of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…g ., [ 14 ]), and the accumulated inflammatory cells, such as eosinophils ( e . g ., [ 15 ]), also release various mediators around the smooth muscle cells. Some of these autocrine/paracrine mediators affect transcriptional signaling in the cells of airway smooth muscle, resulting in an alteration of its function [ 12 , 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…g ., [ 14 ]), and the accumulated inflammatory cells, such as eosinophils ( e . g ., [ 15 ]), also release various mediators around the smooth muscle cells. Some of these autocrine/paracrine mediators affect transcriptional signaling in the cells of airway smooth muscle, resulting in an alteration of its function [ 12 , 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also identified that this response was mediated by p38 MAP kinase and rho kinase signalling that may be amenable to pharmacological intervention [18]. Using a similar sensitization model, Lortie and colleagues [19] [20]. The mechanism(s) by which these cells contract and mediate airway hyperresponsiveness has also been examined recently using precision cut lung slices and Ojiaku and colleagues demonstrated that TGF-β1 may play an important role in mediating contractility via increasing basal and carbachol-induced bronchoconstriction [21] via a smad3 dependent mechanism.…”
Section: In Vivo Studies Of Obese Asthma Phenotypesmentioning
confidence: 96%